The Influence of Green Management, Stock Market Segmentation, Operating Cash Flow and Company Characteristics on Profit Management - Nico Valentino (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
The study examines the impact of green management, stock market segmentation, operating cash flows, and firm characteristics on earnings management. Earnings management is measured using the modified Jones Model. The study employs purposive sampling and includes 86 companies listed on the Indonesian Stock Exchange between 2018 and 2022. There are 285 observations used to test the hypothesis using the panel regression method. The research findings indicate that green management has a positive effect on profit management, whereas corporate size has an adverse effect. However, factors such as stock market segmentation, operating cash flows, return on assets, and dividend yield do not have a significant impact on profit management. These findings indicate that companies implementing green management systems are more likely to uphold their reputation by generating higher income.